The impact of physico-chemical properties of the jet fuel and biofuels on the characteristics of gas-turbine engines - Sh. Ardeshiri (Научный вестник МГТУ ГА)
The current development trend of global civil aviation is the growth of passenger and freight traffic, which entails the consumption of jet fuel. Under these conditions, increasing the efficiency of jet fuel used is of great importance. Global energy consumption is constantly growing, and, first of all, the question of diversification of oil resources arises, resources from which the bulk of motor fuels is produced. Other types of raw energy sources (natural gas, coal, bio-mass) currently account for only a small part. However, an analysis of the development of jet fuels indicates that work is underway to obtain these from other sources of raw materials, especially bio-fuels. Much attention is given to obtaining bio-fuels from renewable sources – such as algae. The issue of the mass transition of civil aviation to alternative fuels is complex and requires the solution of intricate technical as well as economic issues. One of these is the assessment of the impact of new fuels on GTE performance. It is important to give an objective and quick assessment of the use of various types of fuels on the main characteristics of the engine – i.e., throttle and high-speed characteristics. In this case, it is necessary to take into account chemical processes in the chemical composition of new types of fuel. To assess the effect of fuels on the characteristics of a gas turbine engine, it is proposed to use a mathematical model that would take into account the main characteristics of the fuel itself. Therefore, the work proposes a mathematical model for calculating the characteristics of a gas turbine engine taking into account changes in the properties of the fuel itself. A comparison is made of the percentage of a mixture of biofuels and JetA1 kerosene, as well as pure JetA1 and TC-1 kerosene. The calculations, according to the proposed model, are consistent with the obtained characteristics of a gas turbine engine in operation when using JetA1 and TC-1 kerosene. Especially valuable are the obtained characteristics of a gas turbine engine depending on a mixture of biofuel and kerosene. It was found that a mixture of biofuel and kerosene changes the physicochemical characteristics of fuel and affects the change in engine thrust and specific fuel consumption. It is shown that depending on the obtained physicochemical properties of a mixture of biofuel and kerosene, it is possible to increase the fuel efficiency and environmental friendliness of the gas turbine engines used.